Ensino superior: um estudo sobre a política de assistência estudantil na trajetória da UFOPA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
The present study has as its theme, “Higher education: a study on the policy of student assistance in the trajectory of Ufopa”. The research proposal was limited to the three Units of the Institution located in the Municipality of Santarém-Pa: Tapajós Unit, Rondon Unit and Amazon Unit. The analyzes pertinent here are based on the historical process of insertion of higher education in Brazil, going through the policies of the student's permanence in the Universities over time, until reaching the main focus of this investigation, which is the approach with the Ufopa actors, directly involved with the management of student assistance in the academic environment. The analysis discusses the meanings of the student assistance policy, its materiality, the right to education, permanence in university and equity. It is a qualitative research with quantitative data, based on the historical-dialectical materialism method, understood here as the most appropriate for this type of approach, for allowing a better contextualization of the investigated object. As a problem to be solved by this study, it was asked: "How did the Student Assistance Policy of the Federal University of Western Pará materialize throughout its trajectory?" Thus, the central objective is to analyze the process of implementing the student assistance policy at the Federal University of Western Pará, in its historical path. As instruments that will support this study, some institutional documents were used, such as resolutions, legislation, management reports, budget tables and institutional histories, in addition to semistructured interviews with administrative technicians, managers and ex-managers of the Pro-rectory of Student Management, as well as informal conversations and questionnaires applied on the Google Forms platform for students with active links at Ufopa, who are users of student assistance. As a preliminary hypothesis, it is stated that it is possible to identify in the Institution some constraints to the equalization of human rights to education, given that in view of the political context, student assistance is sometimes linked much more to the logic of service than to law. Even so, it can be seen that there is a relationship between the receipt of aid and the performance of assisted students, since, according to the analysis of secondary data, it was evident from the reports, the improvement in the academic performance coefficient, after receiving the assistance aids. The results obtained indicate that although there is a need to expand in quantitative and qualitative terms, the student assistance programs existing at Ufopa are of great importance for the permanence of students in conditions of socioeconomic vulnerability.
Keywords: Ensino Superior; Assistência Estudantil; Políticas Públicas; Permanência; CNPQ::CIÊNCIAS HUMANAS; Políticas públicas e estratégias de desenvolvimento regional